Group Counseling Services for Employees PT Djarum Central Lombok - Baiq Mahyatun (RedwhitePress)
The progress in science and technology as well as the rapid flow of information bring influence and change a very complex against the order of social life and human society. The change can bring the community to a better life or otherwise delivers human problems than can lead to frustrating. Individuals need a container that can be a place to get solution of various problems or issues they experienced. One of the containers it is guidance and counseling. Guidance and counseling have different types of service; one of the service types is group counseling services. Execution of counseling services for employees of PT Djarum group in Central Lombok bring positive impact seen from the results of the now given to the participants after the service implemented. The participants fell relieved, pleased and fell benefits of the activities of the counseling services group, and recommends that this activity continues and if possible this Group counseling is carried out for the leadership of their.